Political Economy and MUI Fatwa No. 83 of 2023: Literature Review - Agung Prayogo; Rakhmat Syawal; Adi Pia; Devrichan Syahputra Zalukhu; Elly Warnisyah Harahap (Institute of Advanced Knowledge and Science, 2024)
This research is a literature review which aims to analyze the relationship between political economy and MUI Fatwa No. 83 of 2023. Through searching for the keywords